(3Yhf GdQMef aj MaX GdbQBf HRjGOI aJM GdefGf aj Med GdaQbGf (B/s - (3CHj PQ Gdbdehfj, YHO GdefYe Hf MSjf Hf Mfajs ((3GdbGgQI (B:s (3GdecJHI GdJhajbjI ,s, 1900)
(3jJfGhd cJGH (B((3Yhf GdQMef aj MaX GdbQBf(B) (3hGdPj bGe HJCdjag CHj PQ Gdbdehfj, ehVhY (B((3MaX GdbQBf GdcQje(B) (3gPG GdcJGH LeY ajg eLehYI cHjQI ef aVGFd hKeQGJ MaX GdbQBf GdcQje, GdJj SjMUd YdjgG GdMGaX Ef TGA Gddg, CQGO Hg eDdag Cf jHjf HWQjbI SdSdI hhGVMI, def jQjO MaX GdbQBf cjajI GdbjGe HPdc HTcd jSgd ageg ddeJdbj, ceG Cfg jhVM ddMGaX cjajI JKHjJ MaXg MJi dG jfSGg HYO eOI, hjXd QGSNG aj Pgfg(B. s
Keywords: (3GdbQBfs -- (3MaX GdbQBfs -- (3JYdje GdbQBfs